Perancangan Pillar Slewing Jib Crane SWl 2 Ton dan Span 5 Meter - Laurensiana Devi; I Putu Sindhu Asmara; Pranowo Sidi (Proceedings Conference On Design Manufacture Engineering And Its Application, 2022)
Machining process at PT Lintech Duta Pratama had always delays because a hoisting appliance unsuitable in terms of design and mechanism, so it was decided to designed a pillar slewing jib crane type of hoisting appliance with a design in accordance the workshop layout and a slewing mechanism to can moving material. The design method used the Ulrich method by creating design concepts, then will be selected the best design according to the selection criteria in terms of functionality, strength, and cost, and analysis of structural strength with manual calculation and simulation using Autodesk Fusion 360software. Analysis of the strength on the selected design concept obtained a bending stress value of 77.06 N/mm2 on the jib, 128.80 N/mm2 on the pillar, 155.30 N/mm2 on the arm and the slewing mechanism can be controlled by remote, the components used are gear motors, spur and pinion gear, bearings, shafts and limit switches. Further research can make material variations on the structure in order to get cheaper and stronger results, plan electrical components on the slewing mechanism, and plan the hoisting mechanism and traveling mechanism on the pillar slewing jib crane.